PENGARUH MOTIVASI, KOMPENSASI DAN KOMPETENSI TERHADAP KINERJA (Studi pada Karyawan PT PEGADAIAN (Persero) Cabang Poncol) - Dian Ayu Vidya Kumalasari, 14.05.51.0287; Suko Priyono, Bambang (Students Journal of Economic and Management, 2018)
The success of a company is strongly influenced by employee performance. Every company will always try to improve the performance of its employees to achieve company goals. Factors that can improve employeeÂ  performance are motivation, compensation and competence. The purpose of this study is, (1) To analyze the influence of motivation on employee performance. (2) To analyze the effect of compensation on employee performance. (3) To analyze the influence of competence on employee performance. The population in this research is all employees of PT Pegadaian (Persero). Samples taken are all employees of PT Pegadaian (Persero) Branch Poncol that there are as many as 102 respondents. The independent variables and bound in this research are Motivation (X1), Compensation (X2), Competence (X3) and Performance (Y). The instrument used is a questionnaire. Instrument validity test using factor analysis, reliability test using Alpha Cronbach. After that the collected data was analyzed by multiple regression analysis method. The conclusion of this research are (1) motivation have positive effect to performance. (2) Compensation has no effect on performance. (3) Competence has a positive effect on performance.Keywords: Motivation, Compensation, Competence, Performance